ANALISIS KESALAHAN EJAAN PADA MAKALAH MAHASISWA STKIP AL HIKMAH SURABAYA (KAJIAN MATA KULIAH BAHASA INDONESIA) - Prasetya, Ady Dwi Achmad (Jurnal Lentera merupakan Jurnal Prodi Pendidikan Bahasa Indonesia yang berkala mempublikasikan artikel ilmiah dari hasil penelitian berupa pengajaran dan pendidikan Bahasa Indonesia. Secara khusus, jurnal ini berisi penelitian tentang pengajaran, pen, 2019)
Abstract The aim of this research is to describe: (1) The misuse of capital letter; (2) The misuse of prefix and affix; and (3) The misuse of punctuation on students’ paper at STKIP Al Hikmah Surabaya. This paper used descriptive qualitative. The sample of this research was 6 papers, which were: 2 papers from elementary teacher department, 2 papers from English teacher department, and 2 papers from Physics teacher department. The data collection technique used was documentation. The instrument used was document, that is the students’ paper. The result of the research showed that the total number of spelling error was 150, which consists: (1) the misuse of capital error was 25 numbers; (2) the misuse of prefix di- and ke- was 13 numbers, which was 11 misuse for prefix di- and 2 misuse for ke-, moreover there were no mistake on the use of prefix di-, ke-, and  dari; (3) the misuse of punctuation  was 112 total numbers, which consists 33 misuse of point, 67 misuse of comma, 3 misuse of hyphen, and 6 misuse of colon. Keywords: Error Analysis, Spelling, Papers